Knowledge, attitudes and practice of last-year dental students in Rio de Janeiro city on HIV/AIDS - Chagas, Wagner Pinto das; Rodrigues, Bruno Teixeira Gonçalves; Israel, Mônica Simões (Journal of Oral Diagnosis, 2019)
HIV pandemic remains a serious public health issue in the world; Brazil stands out as one of the countries with the highest rates of infected people. The continuous advancement in the understanding of HIV infection, and its forms of transmission and treatment, hasnt necessarily been accompanied by a change in the behavior of the general population, especially of health agents. These, in the performance of their professions, need to be conscious of the deep impact that the condition still holds throughout all of the gradua- tion courses and clinical studies. Therefore, they should ally knowledge about the disease and the mastery of safety practices to attitudes that respect their patients. The present study aims to analyze the behavior of students of the last year Dental students of two Universities from Rio de Janeiro regarding the care of people living with HIV/AIDS, reinforcing the importance of the inclusion of the dental practitioner in the multidisci- plinary team of the study and treatment of the disease. Although 58.3% of the students declared contact with HIV/AIDS patients, only 13.4% had previous training in the care of these patients. It is urgently necessary to add a specific didactic module on HIV/AIDS in the school curriculum.